2022
DOI: 10.1267/ahc.21-00081
|View full text |Cite|
|
Sign up to set email alerts
|

Histomorphological Changes in a Rat Model of Polycystic Ovary Syndrome and the Contribution of Stevia Leaf Extract in Modulating the Ovarian Fibrosis, VEGF, and TGF-β Immunoexpressions: Comparison with Metformin

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disorder of fertile females. It has been reported that stevia leaf extract (SLE) has antidiabetic and antihyperlipidemic properties. Therefore, the current study hypothesized and investigated the role and mechanistic aspects of a natural sweetener; SLE in treating a rat model of letrozole-induced PCOS and to compare it with metformin. Thirty-five female Wistar albino rats were divided into 5 groups: control, PCOS-induced group (letrozole, 1 mg/kg/d, for 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…A thorough literature search for antioxidant activity of stevia resulted in 184 articles. After screening of titles and abstracts, and compliance with the PRISMA guidelines (http://www.prisma-statement.org/ (accessed on 26 January 2023)) (Figure 2), 22 articles were found to satisfy the eligibility criteria [41,42,44,45,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]. Seventeen records were additionally retrieved from screening lists of references, and two of them [37,73] were enrolled in the meta-analysis, making a total of 24 articles, which contained 104 studies in total.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…A thorough literature search for antioxidant activity of stevia resulted in 184 articles. After screening of titles and abstracts, and compliance with the PRISMA guidelines (http://www.prisma-statement.org/ (accessed on 26 January 2023)) (Figure 2), 22 articles were found to satisfy the eligibility criteria [41,42,44,45,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]. Seventeen records were additionally retrieved from screening lists of references, and two of them [37,73] were enrolled in the meta-analysis, making a total of 24 articles, which contained 104 studies in total.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…There were also significant decreased cystic follicles. The improved ovarian histoarchitecture could be related to the antiandrogenic property of the treatment options [40] .…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference between these treatments and metformin treatment for the amount of Masson-stained collagen fibers and TGF-0 immune-expression. Literature has suggested that metformin has an antifibrotic impact in a number of organs, including the ovarian fibrosis caused by dehydroepiandrosterone [40] .…”
Section: Discussionmentioning
confidence: 99%
“…For each image, a line was drawn to mark the granulosa and theca cell layers, and then analyses and set measurements were performed to determine their thickness. Finally, the mean values from each slide were calculated (Morsi et al., 2022). In addition, intestinal claudin‐1 staining intensity was assessed by processing images of intestinal sections to determine the intensity of claudin‐1 staining.…”
Section: Methodsmentioning
confidence: 99%